Suicide and Suicide Attempts in Elderly Patients: An Epidemiological Analysis of Risk Factors and Prevention - Makara-Studzińska, Marta; Somasundaram, Siva G.; Halicka, Joanna; Madej, Agata; Leszek, Jerzy; Rehan, Mohd; Ashraf, Ghulam M.; Gavryushova, Liliya V.; Nikolenko, Vladimir N.; Mikhaleva, Liudmila M.; Muresanu, Cristian; Kirkland, Cecil E.; et al. (Current Pharmaceutical Design, 2021)
A number of elderly patients commit suicide due to the interaction of various factors, including, for example, feelings of loneliness, financial distress, alcohol abuse, chronic pain, progressive diseases, and personality disorders. The data from the EU countries with the highest rates of suicide and suicide attempts among people over 55 years of age warrant the consideration of new approaches to address this social problem. Methods: PubMed and other databases, including Polish National data, were used for the analyses. Results: The average European suicide-attempt rate is 18 per 100 thousand inhabitants. More cases of suicides were reported among those over 55 years of age. Suicide attempts from the year 2012 to 2014 and deaths in 2012 have been reviewed. The risk factors involved in these events, such as depression and social situations including loneliness, health condition, etc., have been discussed to suggest a plausible preventative approach for this important elderly problem. Conclusion: The psychophysiology of elderly persons affected by retirement, socio-economic changes, limited personal autonomy, loneliness, lack of support by the family, and diseases ultimately may lead elderly patients to commit suicide. Thus, financial freedom, family support (respect, love, and care), proper medications, psychological and psychiatric interventions may help the elderly avoid suicidal thoughts and prevent attempts.
Keywords: gerontology